Pengaruh Motivasi Pengetahuan Perpajakan dan Motivasi Peningkatan Kualitas Diri Terhadap Minat Mahasiswa Akuntansi untuk Mengikuti Brevet Pajak - Suyanto, Suyanto; Ania, Ainun (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of tax knowledge motivation and self-improvement motivation on students' interest in taking tax brevets. The independent variables this study are tax knowledge motivation and self-improvement motivation. While the dependent variable is the student's interest in taking tax brevets. The research population are 2019, 2020 and 2021 accounting students in Indonesia. The collection of data used primary data and obtained by distributing questionnaires through the Google form. Data collection use is sample of 360 respondents with convenience sampling. Data analysis in this study use multiple linear analysis and the processed using IMB SPSS version 20. Keywords: Tax Knowledge Motivation, Self-Quality Improvement Motivation, Students' Interest in Joining Tax Brevet